1998
DOI: 10.1046/j.1365-2648.1998.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention with international nurses and changes in knowledge, attitudes and willingness to provide care to patients with HIV/AIDS

Abstract: This paper reports the findings of a study which examines the relationship between the use of an educational intervention with nurses from several Asian countries and changes in knowledge, attitudes and willingness to care for patients with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). A pre-test and post-test questionnaire was used to collect the data. The results indicate, that whilst there was an improvement in knowledge following the educational intervention, there is a need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 15 publications
4
45
0
1
Order By: Relevance
“…Many studies suggested that, shortages of materials and staff and heavy workload were important factors influencing the implementation of universal infection control. 3,5,18,34 Stone et al reported that poor working conditions and high work load were important risk factors for nurses being injured with medical equipment such as needles by 50-200%. 35 Some HCPs in our study were misinformed about HIV/ AIDS before they took part in the training program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies suggested that, shortages of materials and staff and heavy workload were important factors influencing the implementation of universal infection control. 3,5,18,34 Stone et al reported that poor working conditions and high work load were important risk factors for nurses being injured with medical equipment such as needles by 50-200%. 35 Some HCPs in our study were misinformed about HIV/ AIDS before they took part in the training program.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies reported that infection fear,misinformation or lack of information of healthcare providers had negative consequences such as humiliating the patient and even refusing to give treatment. 34,37 In addition, HCPs were reoprted to be influenced by cultural norms. 34,37 The study results demonstrated that some of the HCPs believed that patients should know their HIV status and this information should be shared with other HCPs and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported an association between a high level of knowledge and positive attitudes among nurses (McCann & Sharkey, 1998;Uwakwe, 2000). Nurses need to be updated on HIV knowledge that could boost morale in HIV care because attitude seems to be positively correlated with knowledge Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…That study also notes that the fear of HIV infection decreased as knowledge levels rose. McCann and Sharkey (1998) note in a similar study that following an educational intervention with nurses regarding HIV transmission routes, participants were more willing to work with a colleague who was HIV positive, and to treat patients who are HIV positive. These same participants, however, would, 'take additional precautions for fear of contracting HIV in the workplace ' (p. 267).…”
mentioning
confidence: 96%